Pengaruh Lingkungan Kerja Fisik Terhadap Kepuasan Kerja Karyawan Toko Mas Rahayu Batujajar - Sela Eudia Siregar; Mochamad Vrans Romi (Journal of Economic, Bussines and Accounting (COSTING), 2024)
This research aims to determine the effect of the physical work environment on employee job satisfaction at the Rahayu Batujajar mas shop. The research instruments used have passed validity and reliability tests. Data collection was carried out through interviews and questionnaires with employee respondents. Participation in this research involved 80 respondents using data collection techniques field research with simple random sampling. Data analysis uses a quantitative descriptive approach, validity testing, reliability testing and simple linear regression with the help of software statistik diprogram of social science (SPSS) version 27. These two hypotheses were strengthened by a one-party test of acceptance and rejection between the physical work environment on employee job satisfaction. These results indicate that the physical work environment has a positive effect on employee job satisfaction. The findings of this research can provide benefits for companies and management as consideration in making decisions regarding the physical work environment and job satisfaction.